Effects of disinfection and sterilization on the dimensional changes and mechanical properties of 3D printed surgical guides for implant therapy - pilot study - Gréta Török; Péter Gombocz; Eszter Bognár; Péter Nagy; Elek Dinya; Barbara Kispélyi; Péter Hermann (BMC, 2020)
Abstract Background The purpose of this research was to investigate the effects of disinfection and three different sterilization methods on the dimensional changes and mechanical properties of three-dimensional (3D) printed surgical guide for implant therapy. The objective was to assess the effects of sterilization procedures in 3D printed drill guide templates with destructive and non-destructive material testing. Methods Fifteen identical drill guide templates were produced using a 3D printer. The surgical guides were classified into five groups: three controls, three disinfected (4% Gigasept®, 60 min), three plasma sterilized, three autoclave sterilized (+ 1 bar, 121 °C, 20 min), and three autoclave sterilized (+ 2 bar, 134 °C, 10 min). The templates were digitalized with a Steinbichler SCAN ST 3D scanner. Length was measured under an SZX16 stereomicroscope. A scanning electron microscope was used to study the surface morphology of the drill templates. The hardness, and flexural and compressive strength were measured to assess any changes in the physical characteristics of the material caused by sterilization. The drill guide templates were also examined with a Dage XiDAT 6600 X-ray. During the X-ray examinations, the following parameters were used: 100 kV voltage, 128 AVG averaging, 0.8 W power. One-way analysis of variance (ANOVA) was used to detect the difference between groups. Results Evaluation of the hardness measurements of the various specimens shows that the hardness of the material was not changed by the plasma sterilization (p = 0.0680), steam sterilization on 121 °C (p = 0.6033) or disinfection process (p = 0.1399). The statistical analysis revealed significant difference in hardness strength of the autoclave sterilized (134 °C) specimens (p = 0.0002). There was no significant difference between the goups regarding the scanning electron microscopic and stereomicroscopic examinations. There was no significant difference regarding the X-ray visibility of the templates to the effect of the disinfection (p = 0.7844), plasma sterilization (p = 0.4091) and steam sterilization on 121 °C (p = 0.9277) and steam sterilization on 131 °C (p = 0.093). The effect of the sterilization was the same in case of both flexural and compressive strength of the material. Conclusions Our findings indicate that plasma sterilization and steam sterilization at 121 °C were both suitable for sterilizing the tested 3D printed surgical guides.